PEER DIRECT FEEDBACK UNTUK MENINGKATKAN KEMAMPUAN MENULIS AKADEMIK MAHASISWA PROGRAM STUDI D3 BAHASA INGGRIS FAKULTAS ILMU BUDAYA UNSOED TAHUN AJARAN 2015/2016 - slamet riyadi (Faculty of Humanities, Universitas Jenderal Soedirman, 2016)
Departing from the reality that the students' competence in academic writing was considered in low level, this study was conducted. In fact students really need that competence since the academic writing competence is required for academic communication. Therefore, the peer direct method is applied in the learning process as an altrernative to improve that condirion. The subjects in this study were 28 students of Academic Writing class of D3 English Diploma Program Faculty of Culture Jenderal Soedirman University. Qualitative Method was applied in the study with case study design. To maintain the validity and realibility of the data, three data collection methods consisting of interview, observation, and questionnaire was conducted. The result of the analysis revealed that peer direct feedback improved students' competence in academic writing. Furthermore, it also improved student ivolvement and classroom activities in the teaching learning process.